Expression and transcriptional activities of nuclear receptors involved in regulation of drug-metabolizing enzymes are not altered by colchicine: focus on PXR, CAR, and GR in primary human hepatocytes - Dvořák, Zdeněk; Maurel, Patrick; Vilarem, M. J; Ulrichová, Jitka; Modrianský, Martin (Cell biology and toxicology, 2007)
Recent findings show that colchicine (COL) in submicromolar concentrations downregulates the expression of major drug-metabolizing P450 enzymes in human hepatocytes. Concomitantly, the expression of pregnane X receptor (PXR) and constitutive androstane receptor (CAR) was diminished by COL, whereas expression of glucocorticoid receptor (GR) remained unaltered. A tentative mechanism is perturbation of the GR-PXR/CAR-CYP2/3 signaling cascade, resulting in restricted transcriptional activity of GR receptor by colchicine. In this work we focused on 10-demethylcolchicine (colchiceine; EIN), a structural analogue and a putative metabolite of COL that lacks tubulin-binding activity. We investigated the effects of EIN on the expression of PXR, CAR, and GR receptors in primary cultures of human hepatocytes. In contrast with the effects of COL, EIN does not alter the expression of PXR, CAR, and/or GR receptors mRNAs. In addition, EIN had no effects on transcriptional activities of PXR, CAR, and GR receptors in reporter gene assays using transfected cell lines. Considering that COL and EIN are structurally very close and differ only in their tubulin-binding activity, the data presented imply that the deleterious effects of COL on the GR-PXR/CAR-CYP2/3 cascade are primarily due to perturbation of the microtubule network. Our data support the idea of replacing COL by EIN, which is less toxic and does not interact with xenoreceptors.
Keywords: hepatocyty; transfekce; exprese genu; Gene Expression; RNA, Messenger; Pharmaceutical Preparations; Receptors, Glucocorticoid; steroidní receptory; Receptors, Cytoplasmic and Nuclear; Transfection; Transcription, Genetic; reportérové geny; Hepatocytes; genetická transkripce; léčivé přípravky; kultivované buňky; lidé; Transcription Factors; Receptors, Steroid; transkripční faktory; Humans; Colchicine; Financing, Organized; kolchicin; Cells, Cultured; Genes, Reporter; receptory cytoplazmatické a nukleární; financování organizované; messenger RNA; receptory glukokortikoidů